Evaluating the psychometric properties of the Immunotherapy module of the MD Anderson Symptom Inventory. Issue 2 (23rd October 2020) - Mendoza, Tito; Sheshadri, Ajay; Altan, Mehmet; Hess, Kenneth; George, Goldy; Stephen, Bettzy; Castillo, Lilibeth; Rodriguez, Enedelia; Gong, Jing; Peterson, Christine; Rodon Ahnert, Jordi; Fu, Siqing; et al.
Abstract : Introduction: Immunotherapies have revolutionized the treatment of various cancers, but little is known about their symptomatic toxicity. Assessing these symptoms is best accomplished by asking the patients themselves. However, such reports are subjective and may face challenges as bonafide scientific data. Demonstrating the validity of symptom assessment tools, mainly through the reduction of measurement errors, has the potential to improve patient care if these tools are widely adopted. To that end, we present herein the psychometric properties of the Immunotherapy for Early-Phase Trials module of the MD Anderson Symptom Inventory (MDASI-Immunotherapy EPT) in patients receiving various immunotherapies in early phase trials at a major cancer center. Methods: One hundred forty-five patients completed the inventory at baseline, with 85 of them also doing so after 9 weeks of treatment. The mean (±SD) age of the patients was 57.0±12.9 years. Also, 56% of the patients were women, 79% identified as white, and 49% had at least some college education. Results: The internal consistency reliability of the MDASI-Immunotherapy EPT was excellent, as the Cronbach's alphas for all of its subscales were at least 0.88 (range 0.88–0.95). Known-group validity based on Eastern Cooperative Oncology Group performance status groupings was excellent at 9 weeks after the start of an immunotherapy trial for the MDASI-Immunotherapy EPT severity (effect size, 0.96) and interference (effect size, 0.82) subscales. We found substantial changes in the symptom items difficulty remembering (effect size, −0.85), fever and/or chills (effect size, −0.63), disturbed sleep (effect size, −0.52), diarrhea (effect size, −0.42), and swelling of hands, legs, or feet (effect size, −0.39). Conclusions: In conclusion, the MDASI-Immunotherapy EPT is a valid, reliable, and sensitive tool for measuring symptomatic toxicity.